Beliefs in the crossroads: Teachers’ personal epistemology and effective practice for culturally and linguistically diverse students - Fanning, Cristina (Kansas State University, 2017)
Today, more than ever, educators throughout the United States need to know more about the challenges, opportunities, and value diversity brings to their schools. In one decade, 2003 to 2013, the population of K-12 public school students who identified as white decreased by 9%, or by 3.2 million. During this same time, the number of Hispanic students in the K-12 public school system increased from 19% to 25%, or by 3.5 million (NCES, 2016). Projections for K-12 student enrollment in public schools indicate a continued decline in the number of White students and increases in students from diverse racial and ethnic backgrounds within another decade (NCES, 2016). We must consider the ways in which we socialize, communicate, and act within these unfamiliar and new spaces – especially those spaces where our beliefs intersect with observable actions in the classroom. The literature is replete with research on teacher epistemologies and culturally responsive teaching, yet research on the dynamic interaction between the two does not exist. Research in this area is needed to better understand how a teacher’s individual epistemology interacts with culturally responsive teaching practices. The purpose of this study was to examine whether individual teacher’s epistemologies, as measured by the Epistemic Belief Inventory (EBI) can predict their level of effective practice with culturally and linguistically diverse (CLD) students, as measured by the Biography-Driven Practices (BDP) rubric. Further, five subscales of the EBI – Simple Knowledge, Certain Knowledge, Innate Ability, Omniscient Authority, and Quick Learning – were examined individually to test for potential correlations. Results show that, overall, a teacher’s epistemic beliefs do not predict their level of effective practice at a statistically significant level; however two subscales, Simple and Certain Knowledge significantly predicted effective practice with CLD students.
Keywords: Education; Culturally responsiveEpistemology